A novel oxidation–reduction route for successive ionic layer deposition of NiO1+x·nH2O nanolayers and their capacitive performance. (April 2016) - Lobinsky, A.A.; Tolstoy, V.P.; Gulina, L.B.
Graphical abstract: Highlights: Presented a novel method of solution synthesis of NiO1+ x · n H2 O. Synthesized product is formed by nanosheets with thickness of 6–12 nm. Electrodes for supercapacitors based on synthesized layers shows high capacity. Abstract: Successive ionic layer deposition (SILD) of NiO1+ x · n H2 O nanolayers was first performed by an oxidation–reduction route using a Ni(NO3 )2 and K2 S2 O8 aqueous solutions. The obtained nanolayers were characterized by SEM, EDX, XRD, XPS, UV–vis and FTIR spectroscopy and electrochemical techniques. The results showed that the as-synthesized product is formed by nanosheets with a thickness of 6–12 nm, having cubic crystal structure of NiO and rhombohedral structure of γ-NiOOH. Electrochemical characterization of the sample prepared by 100 cycles of SILD indicated a capacitive behavior with the specific capacitance value of 1015 F/g at a current density of 1 A g −1 in 1 mol L −1 KOH aqueous solution. Repeated cycling for 3000 charge–discharge cycles demonstrate 10% capacitance fade relative to the initial values. The presented convenient route of synthesis may be used for the preparation of NiO1+ x · n H2 O nanolayers with high surface area and a large capacitance.